Kajian Terhadap Implementasi Pasar Lelang Komoditi Agro pada Dinas Perindustrian dan Perdagangan Provinsi Bali - RICCO DAMONA; I DEWA GEDE RAKA SARJANA; I GUSTI AYU AGUNG LIES ANGGRENI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2013)
ABSTRACT The Study on Implementation of Agro Commodities Auction Market in The Industry and Trade Service of The Province of Bali In the marketing of agricultural products, the most common problem was the gap of unfair of price that accepted by producer farmers by prices paid by the final consumer. Various reasons that lead to margin of trading system, that are weak bargaining position of farmers, farmers tend subject to the buyer rule, the cost of transport from production centers to the end of consumer market. Work program in the Industry and Trade service of the Province of Bali was conduct activity of agro commodities auction market, which is one of medium to aid to facilitate the meeting of buyers and sellers directly. The aim of this study was to find out the implementation of agro commodities auction market conducted by the Industry and Trade service as well as the constraints in conduct activity of the agro commodity auction market. Locations of study were selected by purposive sampling. Data collected by the method of observation, in-depth interviews and documentary study. Data have been analyzed descriptively. The results of study showed that the performance of auction market not yet to show maximum results. Levels of productivity were very high fluctuation for each implementation. Problems of fail to deliver and fail to pay occur estimated very low integrity and credible participants, the constraints in the implementation of agro commodity auction market was weak underwriting system, uncertain membership, the formulation of quality standards, as well as the types of commodities that enter the auction market. Implication of important policy will be done by formulate quality standards, priorities of traded commodity, and maximize the role of private sector. Keyword: auction market, agro commodities, implementations.